Fulfillment of Income Tax Obligations for Foreign Workers Working in West Sumatra - Gusminarti; Khairani; Hendria Fithrina; Alfi Thoriq Al Hasan (Jurnal Sakato Ekasakti Law Review, 2026)
Foreign workers (TKA) who work and receive income from Indonesia are subject to income tax (PPh). As income tax payers, TKA are required to comply with these tax regulations. In West Sumatra, there are currently 77 (seventy-seven) companies that employ TKA, with work locations spread across the region. Foreign workers employed in West Sumatra are also subject to income tax regulations. One issue that has been encountered is that some foreign workers leave the company before completing their employment contract, resulting in their tax calculation not covering a full tax year. Given this finding, who is responsible for fulfilling their income tax obligations, the company or another party? The research questions in this study are: 1. What is the mechanism for employing foreign workers in West Sumatra? 2. How are the income tax obligations of foreign workers employed in West Sumatra fulfilled? 3. What efforts has the West Sumatra government made to improve foreign workers' compliance with income tax obligations? The research method used is socio-legal with the required data being primary and secondary data. The data collection techniques are document studies and interviews as well as qualitative data analysis.